Selection criteria for materials to be applied in cryogenic precision equipment engineering - Bosin, M.E.; Lavrentyev, F.F.; Nikiforenko, V.N.; Solodilov, S.A. (Functional Materials, 2006)
Experimental data on temperature effects on the Maksutov coefficient being a preliminary criterion of the material suitability for astro-mirror manufacturing have been summarized for materials of promise for cryogenic optical systems and precision equipment. The material that meets the cryogenic optics requirements to the greatest extent has been noted. Experimental data on low-temperature cycling and dimensional stability of materials used in the field of measuring engineering have been analyzed. Для матерiалiв, перспективних у крiогенних оптичних системах та прецизiйних пристроях, узагальнено експериментальнi данi щодо впливу температури на коефiцiєнт Максутова, що становить попереднiй критерiй придатностi матерiалу для виготовлення астродзеркал. Вiдзначається, який з них за комбiнацiєю властивостей лiпше вiдповiдає вимогам криогенної оптики. Розглянуто експериментальнi данi щодо циклування i розмiрно:i стабiльностi матерiалiв, що використовуються у вимiрювальнiй технiцi. Для материалов, перспективных в криогенных оптических системах и прецизионных устройствах, обобщены экспериментальные данные по влиянию температуры на коэффициент Максутова, являющийся предварительным критерием пригодности материала для изготовления астрозеркал. Отмечается, какой из них по комбинации свойств лучше удовлетворяет требованиям криогенной оптики. Рассмотрены экспериментальные данные по низкотемпературному циклированию и размерной стабильности материалов, используемых в измерительной технике.